2013
DOI: 10.3109/14756366.2013.800058
|View full text |Cite
|
Sign up to set email alerts
|

New spiroindolinones bearing 5-chlorobenzothiazole moiety

Abstract: In this study, 5-chloro-3H-spiro-[1,3-benzothiazole-2,3 0 -indole]-2 0 (1 0 H)-one derivatives 3a-l were synthesized by the reaction of 1H-indole-2,3-diones 1a-l with 2-amino-4-chlorothiophenol 2 in ethanol. 3a-l were tested for their abilities to inhibit lipid peroxidation (LP), scavenge DPPH and ABTS þ radicals, and to reduce Fe 3þ to Fe 2þ . Most of the tested compounds exhibited potent scavenging activities against ABTS þ radical, reducing powers and strong inhibitory capacity on LP. 3 a, 3 d, 3e, 3h, 3j a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…62 DPPH, ABTS, and anti-liposomal peroxidation tests were assessed for spiroxindoles C22-C26. 63,64 The results obtained showed that these compounds have EC 50 values of 0.98, 1.30, 13.00, 8.33 and 4.19 mM, respectively, in the DPPH assay, EC 50 of 0.98, 1.02, 0.99, 1.16 and 1.55 mM in the ABTS test and EC 50 of 0.04, 0.03, 0.11, 0.12 and 0.12 mM in the anti-LPO test. Additionally, compounds C22-C26 were compared with vitamin C and tocopherol as positive controls that respectively presented EC 50 values of 0.36 and 0.35 mM in the DPPH test and 1.20 and 1.20 mM in the ABTS test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 DPPH, ABTS, and anti-liposomal peroxidation tests were assessed for spiroxindoles C22-C26. 63,64 The results obtained showed that these compounds have EC 50 values of 0.98, 1.30, 13.00, 8.33 and 4.19 mM, respectively, in the DPPH assay, EC 50 of 0.98, 1.02, 0.99, 1.16 and 1.55 mM in the ABTS test and EC 50 of 0.04, 0.03, 0.11, 0.12 and 0.12 mM in the anti-LPO test. Additionally, compounds C22-C26 were compared with vitamin C and tocopherol as positive controls that respectively presented EC 50 values of 0.36 and 0.35 mM in the DPPH test and 1.20 and 1.20 mM in the ABTS test.…”
Section: Introductionmentioning
confidence: 99%
“…Syntheses of compounds C22-C26 are shown in Scheme 8. 63,64 Likewise, the AO activities of oxindoles C27-C30 were determined by the DPPH radical scavenging test. For compounds C27 and C28, IC50 values were determined, which were respectively 32.50 mM and 0.44 mg mL À1 .…”
Section: Introductionmentioning
confidence: 99%
“…In two early reports, spiroindolinones incorporating a benzothiazole or 5-chlorobenzothiazole moiety (III) (Figure 1) have been described as promising antioxidants with potent scavenging activities against DPPH˙ and (ABTS˙+) radicals and reducing powers and significant inhibitory capacity on lipid peroxidation. Compounds have also been found to be cytotoxic against some cancer cell lines in anticancer screening [16,17]. Likewise, the antioxidant properties of several small spiroheterocyclic molecules have been reported in different papers [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%